If it's not what You are looking for type in the equation solver your own equation and let us solve it.
45+3n=-5n-3
We move all terms to the left:
45+3n-(-5n-3)=0
We get rid of parentheses
3n+5n+3+45=0
We add all the numbers together, and all the variables
8n+48=0
We move all terms containing n to the left, all other terms to the right
8n=-48
n=-48/8
n=-6
| 5(2x-9)=23 | | 23/8x-1=-4 | | 6z+10=94 | | 4(x+2=-12 | | 16x+20=15x=60 | | 2x+18+5x–6=180 | | 4b+2b-2=22 | | 60/x=6/12 | | 2/3+(3/5)m=36/15 | | x+9-7=18x | | 5x-2x+9=9 | | -4(x+8)+-14=2 | | |-3=4-2x^2| | | 8−6x=4x+48 | | t/2-2=-1 | | 9x+10-7x=-5x+10 | | 4/p=11/1 | | p6.5=42.25 | | 6x+5x-10=34 | | –8r+9=–9−2r | | 2(b-10)=-3(b+5) | | 7+5d=-2d | | -21=(n)/(3)+2 | | 4x-3=55+8x | | ⅝=n/n-9 | | 2(x+4)=4·2(x-2)-2x | | 19-u=156 | | -3x+6=5x-9 | | -10m3=12-8m | | x/1.6+31=40 | | 4(a-5)+4a=2(3a+4 | | 4(2x+1)=-8x-2 |